Multiplier Effects of a Balanced Budget - Haavelmo, Trygve (Econometrica, 1945)
It has commonly been argued that public spending, to be a remedy against unemployment, must be deficit spending and not spending balanced by an equal amount of taxes, since, in the latter case, the government would only be taking back with one hand what it gives with the other. One necessary qualification of this statement is, of course, well known, namely, that taxes corresponding to an equal amount of public spending may lead to a redistribution of incomes which, in turn, may lead to a higher level of national consumption at a given level of private investment. The effect of such redistribution, however, depends essentially on whether or not there is any substantial difference in the marginal propensities to consume, as between the various income groups. If, for example, the propensity-to-consume function of the individual is a linear function of personal income the marginal propensity to consume will be constant for all levels of income, and there could be no redistribution effect (unless the redistribution had an effect on private investment). In this latter case it might then be thought that public spending balanced by an equal amount of taxes would have no effect upon total income and employment in the society (apart from a possible effect, indirectly, on the propensity to invest). This commonly made conjecture is, however, false, as has already been pointed out by several writers on the subject.' In a situation with unemployment and idle resources there is a definite employment-creating effect of public outlays even when they are fully covered by tax revenues. And this is true quite